A New Connectedness Trends in Islamic Finance: A bibliometric Analysis of Biodiversity, Sustainability, and Social Impacts: English - Sakdiyah, Nur Halimatus (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2024)
Background: Islamic finance after COVID-19 has become the main focus of Islamic economic observers in paying attention to sustainability. The issue of sustainability is the goal of the Islamic finance process in solving problems such as the scarcity of green biodiversity. Indonesia is a mega biodiversity country that is very beneficial for society. In this case, Islamic biodiversity financing needs attention in order to benefit the social community. The level of measurement of social community utilization through welfare indicators by paying attention to public health.Objectives: This research aims to map the current relevance of Islamic finance in addressing issues on three variables: biodiversity, sustainability, and social impact.Novelty: Through this research, SDG observers can inspire further exploration and linkages so as to analyze sustainable Islamic financial instruments after the SDGs program.Research Methodology/Design: This study uses bibliometric methods with 3 research linkage analyses namely Co-Authorship, Co-Occurance, and Coupling Bibliometrics with databases drawn from dimensions. Using artificial intelligence such as VOSviewer, we uncover publication trends, researchers who focus on these studies, and bibliographic integration in the field.Findings: The results show that there are interrelationships between variables with two Islamic financial instruments being the top two transactions that are interrelated and beneficial to the relationships between variables. This study provides valuable recommendations for future research to enhance our understanding of the implications of other Islamic financial instruments for their relationship with biodiversity, sustainability, and social impact. However, researchers must acknowledge that the exclusively reviewed literature indexed by Scopus is limited. Through this study, the researcher hopes to inspire further exploration and be able to analyze sustainable Islamic financial instruments post-SDG programImplication: This research can have implications for future researchers, state regulations, and companies that focus on sustainability. Megabiodiversity countries can update regulations on the provisions of sustainability standards by adjusting the connection between biodiversity as an asset to achieve sustainability, which will have an impact on the country's society. because the sustainability regulation standards to date are still not well implemented in mega biodiversity countries, one of which is the GRI standard, and UN unit countries can make this connection as a basic reference for programs after SDGs.Keywords: Islamic finance, Biodiversity, Sustainability, social impact,JEL Classification code :F64, Q51,Q56